Grain surface features and clay mineralogy of the quaternary sediments from Western Deccan Trap Region, India, and their palaeoclimatic significance - Joshi, Veena (Acta Geographica Debrecina Landscape & Environment series, 2011)
Quartz sand grains obtained from a deeply gullied topography along the banks of two tributaries of River Pravara in Maharashtra (India) have been examined with a scanning electron microscope (SEM). Quartz grains have been selected after a heavy mineral separation and micro-photographs of each grain were taken at various angles and magnifications. The sediments reveal features resulting from mechanical grinding as well as from chemical alteration. Conchoidal fractures, cleavage planes, grooves, v-shaped indentations etc. are the mechanical features documented on the grains whereas solution pits of varying sizes and intensity, precipitation surfaces, oriented v-pits, solution crevasses and etching are the features of chemical origin. Several evidences indicate that the samples have undergone digenetic changes. Few grains show the features of intense chemical breakdown. The overall assemblages of the grain surface features suggest that the samples have been subjected to subaqueous transport for a considerable period of time. The minor chemical features such as solution pits or semi circular arcuate steps found in abundance on these grains are due to the dissolution of the sediments in a low energy fluviatile environment. For clay mineralogy, fractions between